Torture, Crimes Against Humanity and the Abuse of International Law - Ronald J. Rychlak (Chrześcijaństwo-Świat-Polityka)
In 2014, United Nations Committee Against Torture raised the possibility that the Vatican’s handling of sexual abuse cases involving Catholic priests constituted torture under international law. A victims group even filed a petition with the International Criminal Court accusing Pope Benedict XIV and other Church officials of “crimes against humanity” and urged that they be prosecuted for their alleged role in the crimes.